PERANAN ZAKAT DALAM PENGEMBANGAN PENDAPATAN DAN PENDIDIKAN KELUARGA PETERNAK (Studi Kasus di Desa Kepakisan, Kecamatan Batur,Kabupaten Banjarnegara, Jawa Tengah)THE ROLE OF TITHE IN DEVELOPING INCOME AND EDUCATION OF ANIMAL FARMERFAMILIES(A Case Study at Kepakisan Village, Batur Subdistrict, Banjarnegera Regency, Central Java) - Nuskhi, Muhammad (Pembangunan Pedesaan, 2005)
This research aimed at studying the role of tithe in developing income of animal farmer families and the effect of the tithe on educational continuity of the family members. Result of the research showed that the families (MPZ) received the tithe had food and tak-food outcome in amount of Rp 345,228.80 larger than tak-tithe receiver families (MNZ) Rp 205,152.84. The long tithe fund giving period resulted in the occurrence of life style difference between MPZ and MNZ families. Obviously, there was a tendency that MPZ families had an opportunity to educate on Elementary School level compared to MNZ families.